The process of paragraph writing - Reid, Joy M.; Lindstrom, Margaret (New Jersey: Prentice-Hall, 1985)
1. Punctuation and the basics, 2. sentence structure, 3. The paragraph, 4. Planning the paragraph, 5. The point paragraph outline, 6. The process paragraph and the explanation paragraph, 7. comparison/contrast paragraphs, 8. Cause-effect paragraphs, 9. using and academic library, 10. multiple paragraphs
Incluye bibliografía
Keywords: English Language - Paragraphs